Mechanism of Cobalt-Catalyzed CO Hydrogenation: 2. Fischer-Tropsch Synthesis - Chen, Wei; Filot, Ivo A W; Pestman, Robert; Hensen, Emiel J M (ACS catalysis, 2017)
Fischer-Tropsch (FT) synthesis is one of the most complex catalyzed chemical reactions in which the chain-growth mechanism that leads to formation of long-chain hydrocarbons is not well understood yet. The present work provides deeper insight into the relation between the kinetics of the FT reaction on a silica-supported cobalt catalyst and the composition of the surface adsorbed layer. Cofeeding experiments of C H with CO/H evidence that CH surface intermediates are involved in chain growth and that chain growth is highly reversible. We present a model-based approach of steady-state isotopic transient kinetic analysis measurements at FT conditions involving hydrocarbon products containing up to five carbon atoms. Our data show that the rates of chain growth and chain decoupling are much higher than the rates of monomer formation and chain termination. An important corollary of the microkinetic model is that the fraction of free sites, which is mainly determined by CO pressure, has opposing effects on CO consumption rate and chain-growth probability. Lower CO pressure and more free sites leads to increased CO consumption rate but decreased chain-growth probability because of an increasing ratio of chain decoupling over chain growth. The preferred FT condition involves high CO pressure in which chain-growth probability is increased at the expense of the CO consumption rate.